Corrosion behaviour of X52 steel in the presence of sulphite - C. Fatah, M. (Emerald Group Holdings Ltd., 2014)
Design/methodology/approach-The study was conducted in abiotic solutions containing species typical of sulphate-reducing bacteria (SRB) metabolism. Electrochemical techniques, i.e. linear polarization resistance (LPR), potentiodynamic and electrochemical impedance spectroscopy (EIS), were used to observe the corrosion kinetics and mechanism of X52 steel in the solution containing sulphite. Field emission scanning electron microscope (FESEM) and X-ray photoelectron spectroscopy (XPS) were used to characterize the corrosion products. Purpose â The purpose of this work was to study the corrosion behaviour of X52 steel in the presence of sulphite. Design/methodology/approach â The study was conducted in abiotic solutions containing species typical of sulphate-reducing bacteria (SRB) metabolism. Electrochemical techniques, i.e. linear polarization resistance (LPR), potentiodynamic and electrochemical impedance spectroscopy (EIS), were used to observe the corrosion kinetics and mechanism of X52 steel in the solution containing sulphite. Field emission scanning electron microscope (FESEM) and X-ray photoelectron spectroscopy (XPS) were used to characterize the corrosion products. Findings-LPR and EIS results showed that the addition of sulphite ions to the abiotic solutions increased the rate of X52 steel corrosion. The increase of corrosion rate was due to the increase in the cathodic reaction in the presence of sulphite. It was also observed that sulphite thinned the protective FeS film and caused corrosive species to adsorb on the surface, resulting in an increase in corrosion rate. Originality/value-This paper discusses the effects of sulphite on the corrosion behaviour of X52 steel in abiotic solution containing species typically produced by the SRB-type metabolic process. Irrespective of the presence of sulphide, sulphite is produced by SRB during their metabolic process. However, as far as is known, no published papers are available that discuss the effect of the presence of sulphite as one of the metabolic products of SRB. Â© Emerald Group Publishing Limited.